Good laboratory practice: principles, compliance and mutual recognition, history and OECD framework - Turnheim, Dian (Henry Stewart Talks, 2012)
The OECD Principles of GLP, General introduction to talk series on GLP, compliance monitoring and MAD, Structure of talk series, 1981 OECD Council decision on the Mutual Acceptance of Data, Development and revision of OECD principles of GLP, Role of working group on GLP
Reviewed at 2018/04/19